Highly birefringent nematic and chiral nematic liquid crystals - Woon, K.L.; O'Neill, M.; Vlachos, P.; Aldred, M.P.; Kelly, S.M. (Taylor & Francis, 2005)
We report a simple interference method to determine the dispersion of the extraordinary refractive index and birefringence of highly conjugated and coloured nematic liquid crystals used as light‐emitting materials in organic electroluminescent devices. The measurements are made in the nematic glass phase at room temperature. The birefringence is highly dispersive and values up to 1.1 are obtained. Chiral groups are incorporated into the end chains giving a chiral nematic liquid crystal with a very wide stopband in the visible region. The Berreman matrix method is used to simulate transmission through the chiral nematic liquid crystal cell using the refractive index parameters obtained experimentally. Excellent agreement between theory and experiment is found.